(12x-6)+(16-5x)=

Simple and best practice solution for (12x-6)+(16-5x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12x-6)+(16-5x)= equation:


Simplifying
(12x + -6) + (16 + -5x) = 0

Reorder the terms:
(-6 + 12x) + (16 + -5x) = 0

Remove parenthesis around (-6 + 12x)
-6 + 12x + (16 + -5x) = 0

Remove parenthesis around (16 + -5x)
-6 + 12x + 16 + -5x = 0

Reorder the terms:
-6 + 16 + 12x + -5x = 0

Combine like terms: -6 + 16 = 10
10 + 12x + -5x = 0

Combine like terms: 12x + -5x = 7x
10 + 7x = 0

Solving
10 + 7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 7x = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 7x = 0 + -10
7x = 0 + -10

Combine like terms: 0 + -10 = -10
7x = -10

Divide each side by '7'.
x = -1.428571429

Simplifying
x = -1.428571429

See similar equations:

| 12x+3y+120=180 | | 7-4.5= | | 3(2r+6)=24 | | 9(2x+6)= | | 5d-c=12 | | 8(9x+9)+9(11-x)= | | (4x+1)+(11-4x)= | | 35+50x= | | (4x+13)+(8x-5)= | | 7(8x+5)= | | 3x-5x=-9+x | | 2x^4+7=47 | | 2a+7b-3b+a= | | m+50x=35 | | f(x)=-16x+160x | | 6x+x-8=6x+5 | | 3.2=125x | | 8m-2m=72 | | 5g-5=7 | | -5=-19-n/7 | | 13x-60=83 | | x^6+7x^5+2x^4+9x^3+10x^2-12x-15=0 | | 2/5(x-15)=500 | | c/7+5=-6 | | 24k^2=-24k | | 3x-4x+x-6+2x= | | 8x^2+72a-81=0 | | v/4-9=-3 | | 44-17x=15.60 | | (x+21)+2x=136 | | 2x^2-2x=3x^2-9x | | 180=a+2a+15+a-35 |

Equations solver categories